2021
DOI: 10.1111/jgs.17336
|View full text |Cite
|
Sign up to set email alerts
|

Telephone follow‐up to reduce unplanned hospital returns for older emergency department patients: A randomized trial

Abstract: Background/Objectives: Telephone follow-up calls could optimize the transition from the emergency department (ED) to home for older patients. However, the effects on hospital return rates are not clear. We investigated whether telephone follow-up reduces unplanned hospitalizations and/or unplanned ED return visits within 30 days of ED discharge. Design: Pragmatic randomized controlled trial with allocation by month; odd months intervention group, even months control group. Setting: Two ED locations of a non-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 51 publications
(151 reference statements)
0
14
0
Order By: Relevance
“…The trial was conducted in the EDs of Haaglanden Medical Center (HMC), a non-academic teaching hospital in the Netherlands, from February 1, 2018 to July 1, 2019. In this RCT, 3175 patients were allocated to either the intervention ( n = 1516) or the control ( n = 1659) group, according to the month of their ED visit; patients included in odd months received an intervention telephone call to identify post-discharge problems and to offer additional information, and patients included in even months received a satisfaction survey telephone call [ 20 ]. The Medical Ethics Review Committee of HMC waived the necessity for formal approval of the study as it closely followed routine care (METC Zuidwest Holland, nr.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The trial was conducted in the EDs of Haaglanden Medical Center (HMC), a non-academic teaching hospital in the Netherlands, from February 1, 2018 to July 1, 2019. In this RCT, 3175 patients were allocated to either the intervention ( n = 1516) or the control ( n = 1659) group, according to the month of their ED visit; patients included in odd months received an intervention telephone call to identify post-discharge problems and to offer additional information, and patients included in even months received a satisfaction survey telephone call [ 20 ]. The Medical Ethics Review Committee of HMC waived the necessity for formal approval of the study as it closely followed routine care (METC Zuidwest Holland, nr.…”
Section: Methodsmentioning
confidence: 99%
“…Patients aged ≥ 70 years who were discharged from one of the EDs of HMC to an unassisted living environment were eligible for inclusion. Exclusion criteria were: admission to the hospital, discharge to a nursing home, another care facility or assisted living environment, and planned follow-up appointment at an outpatient clinic or at the ED within 24 h [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although prior studies of ED-directed callback programs have shown that they can improve outpatient follow-up, the association of these programs with ED revisit rates and hospitalization rates have been mixed. Like Fruhan and Bills, Luciani-McGillivray et al found that their program decreased the number of unplanned ED revisits, whereas other callback programs had no association with ED revisits, hospitalizations, or costs of care . Future research is needed to understand this variation.…”
mentioning
confidence: 99%